Neuropsychiatric side effects of cyclobenzaprine. (2nd May 2013) - Shprecher, David; Sloan, Colgan T; Sederholm, Benson
Abstract : Cyclobenzaprine is commonly used as a muscle relaxant and analgesic. Given its tricyclic properties, serotonin syndrome is a potential side effect of this drug. We report an unusual case of a patient who experienced symptoms of delirium and hyperkinetic movement disorders shortly after initiating treatment with cyclobenzaprine and oxycodone. Symptoms resolved within 48 h of discontinuing cyclobenzaprine. This case serves to remind clinicians to monitor for serotonin syndrome when initiating cyclobenzaprine, and when adding opiate or antidepressant medications to the regimen.